Peri-operative morbidity associated with radical cystectomy in a multicenter database of community and academic hospitals. - Luke T Lavallée; David Schramm; Kelsey Witiuk; Ranjeeta Mallick; Dean Fergusson; Christopher Morash; Ilias Cagiannos; Rodney H Breau (PLoS ONE, 2014)
OBJECTIVE: To characterize the frequency and timing of complications following radical cystectomy in a cohort of patients treated at community and academic hospitals. PATIENTS AND METHODS: Radical cystectomy patients captured from NSQIP hospitals from January 1 2006 to December 31 2012 were included. Baseline information and complications were abstracted by study surgical clinical reviewers through a validated process of medical record review and direct patient contact. We determined the incidence and timing of each complication and calculated their associations with patient and operative characteristics. RESULTS: 2303 radical cystectomy patients met inclusion criteria. 1115 (48%) patients were over 70 years old and 1819 (79%) were male. Median hospital stay was 8 days (IQR 7-13 days). 1273 (55.3%) patients experienced at least 1 post-operative complication of which 191 (15.6%) occurred after hospital discharge. The most common complication was blood transfusion (n = 875; 38.0%), followed by infectious complications with 218 (9.5%) urinary tract infections, 193 (8.4%) surgical site infections, and 223 (9.7%) sepsis events. 73 (3.2%) patients had fascial dehiscence, 82 (4.0%) developed a deep vein thrombosis, and 67 (2.9%) died. Factors independently associated with the occurrence of any post-operative complication included: age, female gender, ASA class, pre-operative sepsis, COPD, low serum albumin concentration, pre-operative radiotherapy, pre-operative transfusion >4 units, and operative time >6 hours (all p<0.05). CONCLUSION: Complications remain common following radical cystectomy and a considerable proportion occur after discharge from hospital. This study identifies risk factors for complications and quality improvement needs.